Sitting Matters! Differences Between Sitters and Nonsitters at 6 Months' Adjusted Age in Infants At-Risk and Born Preterm. Issue 3 (July 2019) - Jensen-Willett, Sandra; Pleasant, Malinda; Jackson, Barbara; Needelman, Howard; Roberts, Holly; McMorris, Carol
Abstract : Purpose: Sitting delays in infants born preterm compound cognitive and language deficits. This retrospective study examines differences in prematurity-related risk and compares developmental outcomes between sitters and nonsitters at 6 months' adjusted age. Methods: A total of 105 graduates of the neonatal intensive care unit met inclusion criteria. Infant demographic and medical risk profiles and 6-month Bayley Scales of Infant Development-3rd edition (BSID-III) cognitive and language scores were retrieved. Infants who sat with hands free greater than 60 seconds were classified as "sitters." Results: Sixty-nine percent of the sample were nonsitters and were born earlier, had lower birth weights, were chronologically older at follow-up, and spent more days with respiratory support. BSID-III scores were significantly higher in sitters but did not differ by gender, multiple birth, head ultrasound results, payment type, or race/ethnicity. Conclusion: Sitting abilities at 6 months' adjusted age are associated with prematurity risk factors. Cognitive and language scores differ significantly between sitters and nonsitters. Abstract : This retrospective study examines differences in prematurity-related risk and compares developmental outcomes between sitters and non-sitters at 6 months adjusted age.